An Assessment of Endothelial Markers in Patients with Uncomplicated Malaria in Jazan Province, Saudi Arabia - Madkhali A; Dobie G; Mobarki AA; Essawi K; Hakami W; Hakami AR; Nahari MH; Matari YH; Alhazmi R; Alkurbi M; Musawi S; Alyahyawi Y; et al. (International Journal of General Medicine)
Aymen Madkhali,1 Gasim Dobie,1 Abdullah A Mobarki,1 Khaled Essawi,1 Waleed Hakami,1 Abdulrahim R Hakami,2 Mohammed H Nahari,3 Yahya H Matari,4 Raneem Alhazmi,5 Mohammed Alkurbi,6 Shaqraa Musawi,1 Yara Alyahyawi,1 Fatemah A Alhakami,1 Mohammad S Akhter,1,7 Muhammad Saboor,8,9 Ali Hakamy,10 Hassan A Hamali1 1Department of Medical Laboratory Technology, College of Nursing and Health Sciences, Jazan University, Jazan, Saudi Arabia; 2Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, King Khalid University, Abha, Saudi Arabia; 3Department of Medical Laboratory Technology, Najran University, Najran, Saudi Arabia; 4Department of Hematology and Blood Bank, Baish General Hospital, Jazan, Saudi Arabia; 5Riyadh Medical Clinic Complex, Riyadh, Saudi Arabia; 6Department of Laboratory Medicine, Faculty of Applied Medical Sciences, Umm Al-Qura University, Makkah, Saudi Arabia; 7Health Research Center, Jazan University, Jazan, Saudi Arabia; 8Department of Medical Laboratory Sciences, College of Health Sciences, University of Sharjah, Sharjah, United Arab Emirates; 9Research Institute for Medical and Health Sciences, University of Sharjah, Sharjah, United Arab Emirates; 10Nursing Department, College of Nursing and Health Sciences, Jazan University, Jazan, Saudi ArabiaCorrespondence: Hassan A Hamali, Department of Medical Laboratory Technology, College of Nursing and Health Sciences, Jazan University, P.O. Box 1906, Gizan, 45142, Saudi Arabia, Email hhamali@jazanu.edu.sa Aymen Madkhali, Department of Medical Laboratory Technology, College of Nursing and Health Sciences, Jazan University, P.O. Box 1906, Gizan, 45142, Saudi Arabia, Email ammadkhali@jazanu.edu.saBackground: Malaria continues to be a life-threatening disease that affects people in tropical and sub-tropical regions. Endothelial cells play a key role in the pathogenicity and severity of malaria. This study aimed to assess circulating endothelial cell markers and their correlation with routine laboratory parameters and parasite density in malaria patients compared to matched healthy controls.Materials and Methods: This study included 34 patients with non-severe P. falciparum malaria and 34 matched-healthy controls from the Jazan region. Plasma levels of circulating endothelial markers, including (E-selectin, intercellular adhesion molecule-1 [ICAM-1], and vascular cell adhesion molecule-1 [VCAM-1]) were measured in the study cohort.Results: The findings revealed significantly elevated levels of E-selectin, ICAM-1, and VCAM-1 in malaria patients compared to controls. In addition, multivariable analysis indicated that age, hemoglobin levels, platelet counts, prothrombin time, and E-selectin levels were significantly associated with malaria infection, but no association was found between circulating endothelial markers and parasite density.Conclusion: The data suggest a significant role for E-selectin, ICAM-1, and VCAM-1 in the pathogenesis of malaria infection and their potential use alongside laboratory parameters as indicators of endothelial dysfunction in malaria.Keywords: malaria, endothelial cell markers, E-selectin, ICAM-1, VCAM-1, laboratory parameters